Upaya Orang Tua dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Online Masa Pandemi Covid-19 Di SDN Kalipuro - Anggun Miftakhul Jannah; Muhammad Sulistiono; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to find out how the efforts of parents in providing learning motivation to students in the online learning process during the covid-19 pandemic at SDN Kalipuro. This study uses a qualitative research method with a naturalistic inquiry approach. Naturalistic inquiry is a method that shows that the implementation of research occurs naturally in normal situations that are not manipulated by conditions and circumstances and emphasizes natural descriptions, phenomena screening or data collection carried out under reasonable circumstances. In this study it can be seen that the advice and motivation given by parents greatly affect student learning outcomes, students who are always given advice and motivation by their parents will feel more enthusiastic and confident because they feel not only themselves who have the desire to move forward, but also their parents have the same desire, so that the results or learning achievements achieved by students become better even though the learning is done online. Keywords: motivation to learn, parents’ efforts, Pandemic, Covid-19